Сardiac microhemocirculation in experimental myocardium necrosis - Babaeva, A.G.; Чиж, М.О.; Galchenko, S.Ye; Sandomirsky, B.P. (Cardiovascular Research. 2012. 93, Suppl. 1. P. 52., 2012)
Cardiac microhemocirculation in experimental myocardium necrosis
Babaieva A.G., Chizh N.A., Galchenko S.Ye., Sandomirsky B.P. Сardiac microhemocirculation in experimental myocardium necrosis. Cardiovascular Research. 2012. 93, Suppl. 1. P. 52.
Keywords: cardiac microhemocirculation; experimental myocardium necrosis